Diversity and virulence of the fungus Beauveria (Cordycipitaceae) species associated with Gonipterus sp. n. 2 (Coleoptera: Curculionidae) in South Africa - Schröder, Michelle (University of Pretoria, 2024)
Dissertation (MSc (Entomology))--University of Pretoria, 2024.